Spatial genetic patterns in African wild dogs reveal signs of effective dispersal across southern Africa - Tensen, L.; Jansen van Vuuren, B.; Groom, R.; Bertola, L. D.; de Iongh, H.; Rasmussen, G.; Du Plessis, C.; Davies-Mostert, H.; van der Merwe, D.; Fabiano, E.; Lages, F.; Rocha, F.; et al. (Frontiers in Ecology and Evolution, 2022)
Across much of Africa, decades of civil war, land reforms, and persecution by humans have decimated wildlife populations. African wild dogs (Lycaon pictus) have declined dramatically during the past decades, but have shown recent natural recolonisation of some areas. In Angola, they were rediscovered after almost five decades when no surveys were being conducted, and they have recolonised areas in southern Zimbabwe and northern South Africa. Wild dogs were also reintroduced to Mozambique, where only few individuals remained. Against this backdrop, understanding genetic structure and effective dispersal between fragmented populations is essential to ensure the best conservation approaches for the long-term survival of the species. To this end, our study investigated population genetic diversity, differentiation and gene flow of wild dogs across southern Africa, to include areas where they have recently been rediscovered, reestablished or reintroduced. Our results point to four weakly differentiated genetic clusters, representing the lowveld of Zimbabwe/Limpopo, Kruger NP, Angola/KAZA-TFCA, and the managed metapopulation, counterbalanced by moderate levels of effective dispersal on a southern African scale. Our results suggest that if the human footprint and impact can be significantly minimized, natural